The Question of Readability in Avant-Garde Fiction - Susan Rubin Suleiman (Studies in 20th & 21st Century Literature, 1981)
All avant-garde literature is in some sense «unreadable»—that is, unintelligible in terms of prevailing norms of intelligibility. Avant-garde fiction aggressively proclaims its transgressions of traditional narrative «logic,» and thus challenges at the same time the reader's belief in his or her sense-making ability; the reader may react to this threat by counter-attacking, dismissing the text as «unreadable.» Paradoxically, the term «readable» has a negative value in Roland Barthes's terminology, where the «readable text» is opposed to Barthes's idealized notion of the truly modern «writable text.» According to Barthes, the «writable text» refuses commentary, defies all attempt at a logical, systematic reading. This view is a romantic one. Barthes suggests that the only appropriate way to read modern texts is by adopting their fragmentariness, yielding to them in a kind of ecstasy (jouissance). I suggest, however, that at least two other ways of reading such texts are possible, and desirable: one way consists in the discovery of new rules of readability, which admittedly tend to lead to new codifications and a new canon (this, I argue, is what has occurred in the case of Robbe-Grillet's «transgressive» fictions); the other way consists in seeing how modern texts inscribe the question of their «unreadability» within themselves—in other words, how they thematize the opposition between readable and unreadable, unity and fragmentation, order and transgression. Maurice Roche's Compact serves as the text of reference in this latter discussion.
Keywords: avant-garde literature; avant-garde; unreadable; traditional narrative; logic; Roland Barthes; writable text; readable; fragmentariness; jouissance; new canon; transgressiveMaurice Roche; Compact